Pyoderma Gangrenosum : Report Of Four Cases - Mamta; Kanwar Amrinder J; Thami Gurvinder P (Wolters Kluwer Medknow Publications, 2000)
Four male patients of pyoderma gangrenosum were observed over a period of 1 year. Their age ranged between 24 to42 years. No associated systemic involvement could be detected in any of the patients. The response to corticosteroids was excellent. One patient showed dramatic response to high dose corticosteroid pulse.